Hubungan Kehamilan Ibu di Usia Muda dengan Perkembangan Emosi Anak Usia 3-5 Tahun di Puskesmas Kota Kecamatan Jailolo Kabupaten Halmahera Barat - Agnes, Yuniarmi; Widia Shofa Ilmiah (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Maternal age during pregnancy is one of the factors influencing a child's developmental process, particularly in the emotional domain. Pregnancy occurring at a young age often correlates with psychological unpreparedness for parenting roles, which may affect a child's emotional stability. This study aims to identify the relationship between early maternal age at pregnancy and the emotional development of children aged 3–5 years in the working area of the Public Health Center in Jailolo District, West Halmahera Regency. A quantitative approach was employed using a cross-sectional design, involving 40 mothers as respondents. Data were analyzed using Kendall’s Tau-b test. The findings indicate that 55% of respondents experienced pregnancy before the age of 20, and 32.5% of children exhibited signs of emotional instability. A statistically significant relationship was found between maternal age at pregnancy and the emotional development of children (τ = 0.413; p = 0.010). Mothers who experienced pregnancy at a more mature age were more likely to have children with better emotional stability. These findings underscore the importance of providing support for young mothers and parenting education during pregnancy to promote optimal emotional development in children.